2021
DOI: 10.3390/ijms22115415
|View full text |Cite
|
Sign up to set email alerts
|

Carbonized Lysine-Nanogels Protect against Infectious Bronchitis Virus

Abstract: In this study, we demonstrate the synthesis of carbonized nanogels (CNGs) from an amino acid (lysine hydrochloride) using a simple pyrolysis method, resulting in effective viral inhibition properties against infectious bronchitis virus (IBV). The viral inhibition of CNGs was studied using both in vitro (bovine ephemeral fever virus (BEFV) and pseudorabies virus (PRV)) and in ovo (IBV) models, which indicated that the CNGs were able to prevent virus attachment on the cell membrane and penetration into the cell.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…For example, carbonized lysine-nanogels (CNG) have been successfully obtained by pyrolisis of l -lysine hydrochloride. 50 Differently from the reported hyperbranched polylysine, the synthesis does not require any catalyzer or co-precursor. The resulting nanoparticles, defined as nanogels, have been employed without purification and displayed a hydrodynamic diameter of 200 nm with a temperature-dependent morphology .…”
Section: Lysine-based Carbonized Nanoparticlesmentioning
confidence: 93%
See 2 more Smart Citations
“…For example, carbonized lysine-nanogels (CNG) have been successfully obtained by pyrolisis of l -lysine hydrochloride. 50 Differently from the reported hyperbranched polylysine, the synthesis does not require any catalyzer or co-precursor. The resulting nanoparticles, defined as nanogels, have been employed without purification and displayed a hydrodynamic diameter of 200 nm with a temperature-dependent morphology .…”
Section: Lysine-based Carbonized Nanoparticlesmentioning
confidence: 93%
“…49 Used as an anti-TMV agent, ε-poly-L-lysine is, in fact, effective in reducing the infection by tobacco mosaic viruses. 50 Another test about the capability of polylysine to block the viral infection has been carried out on fibroblasts from hamster kidney (BHK 21 (Clone 13)) infected using the herpes simplex virus type 1 (HSV-1) and type 2 (HSV-2). 51 D-and poly-L-lysine of different molecular weights have been tested as antiviral agents by adding them to the cells 10 min before the addition of the virus (Fig.…”
Section: Polylysinementioning
confidence: 99%
See 1 more Smart Citation
“…The assessment of embryotoxicity related to the application of food-based CDs has also been investigated. Traditionally, chicken embryos and zebrafish embryos are the most frequently used models for embryonic assessment [82,126,128,166,174]. For example, Chou et al [126] conducted a study to evaluate the biotoxicity of lysine-carbonized nanogels (Lys-CNGs) using specific-pathogen-free chicken embryos.…”
Section: Safety Assessment Of Food-based Cdsmentioning
confidence: 99%
“…Traditionally, chicken embryos and zebrafish embryos are the most frequently used models for embryonic assessment [82,126,128,166,174]. For example, Chou et al [126] conducted a study to evaluate the biotoxicity of lysine-carbonized nanogels (Lys-CNGs) using specific-pathogen-free chicken embryos. The authors found that the administered dose of Lys-CNGs did not induce teratogenicity, vascular network formation, or organ structure development in chicken embryos.…”
Section: Safety Assessment Of Food-based Cdsmentioning
confidence: 99%